2010
DOI: 10.1053/j.gastro.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Paired Immunoglobulin-Like Receptor B (PIR-B) Negatively Regulates Macrophage Activation in Experimental Colitis

Abstract: Background & Aims Innate and adaptive immune responses are regulated by crosstalk between activation and inhibitory signals. Dysregulation of the inhibitory signal can lead to aberrant chronic inflammatory diseases such as the inflammatory bowel diseases (IBD). Little is known about negative regulation of innate intestinal immune activation. We examined the role of the inhibitory receptor paired immunoglobulin-like receptor B (PIR-B) in the regulation of macrophage function in innate intestinal immunity. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…23 We thus tested the cellular uptake of scCD98-functionalized NPs in bone marrow-derived macrophages (BMDMs), which are primary macrophages that have been widely used because of their homogeneity, proliferation capacity, long lifespan, and ease of harvesting. 24, 25 As shown in Supplementary Figure 8, an assessment of cellular uptake at different time points (0, 1, 3, and 6 h) revealed a time-dependent increase in the FITC fluorescence signals of NPs in BMDMs. After 6 h, green fluorescence was mainly detected in the cytoplasm of almost all cells.…”
Section: Resultsmentioning
confidence: 83%
“…23 We thus tested the cellular uptake of scCD98-functionalized NPs in bone marrow-derived macrophages (BMDMs), which are primary macrophages that have been widely used because of their homogeneity, proliferation capacity, long lifespan, and ease of harvesting. 24, 25 As shown in Supplementary Figure 8, an assessment of cellular uptake at different time points (0, 1, 3, and 6 h) revealed a time-dependent increase in the FITC fluorescence signals of NPs in BMDMs. After 6 h, green fluorescence was mainly detected in the cytoplasm of almost all cells.…”
Section: Resultsmentioning
confidence: 83%
“…Using a different disease model, PIRB-deficient macrophages similarly demonstrate exacerbated proinflammatory cytokine release and autoimmune colitis [49]. Consistent with the hypothesis that LILRB and PIRB expression on myeloid cells suppresses type-1 inflammatory responses, our laboratory demonstrated that PIRB is necessary to maintain the regulatory phenotype of tumor-infiltrating MDSCs [50].…”
Section: Lilrbs Negatively Regulate Myeloid Cell Activationmentioning
confidence: 70%
“…Immunofluorescence analysis was performed as previously described (14, 32). In brief, frozen sections were fixed in 10% acetone for 10 min, rinsed in PBS, blocked with 3% goat serum/PBS for 2 h at room temperature (RT) and incubated with primary Ab rat anti-mouse F4/80 (5 µg/ml; Ebioscience; San Diego, CA) in 3% normal goat serum/PBS.…”
Section: Methodsmentioning
confidence: 99%